2020
DOI: 10.1021/acs.jced.0c00598
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Verified Alcohol Adsorption Isotherms in Nanoporous Materials from Literature Meta-Analysis

Abstract: Systematic collection of replicate experimental data via literature meta-analysis is a powerful approach for assessing the reproducibility of physical properties data. In this paper, we use meta-analysis to examine the adsorption equilibrium of alcohols in porous materials using a collection of more than 500 alcohol isotherm measurements. We report consensus isotherms (after rejecting outliers) using experimentally measured replicates for 11 systems with methanol, ethanol, 1-propanol, or 2-methylpropan-1-ol ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 50 publications
(108 reference statements)
4
48
0
Order By: Relevance
“…Second, the NPM-adsorption-property matrix may have included too much noise for a successful recommendation. It is known from meta-analyses of isotherms catalogued in NIST-ISODB [80,81] that experimentally measured gas adsorption isotherms in NPMs exhibit high variance; this variance is ultimately manifested as noise that limits the success of the recommendation system. Third, the accuracy and reliability of Henry coefficients obtained from isotherms in NIST-ISODB are naturally limited by the source of data in the database itself.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Second, the NPM-adsorption-property matrix may have included too much noise for a successful recommendation. It is known from meta-analyses of isotherms catalogued in NIST-ISODB [80,81] that experimentally measured gas adsorption isotherms in NPMs exhibit high variance; this variance is ultimately manifested as noise that limits the success of the recommendation system. Third, the accuracy and reliability of Henry coefficients obtained from isotherms in NIST-ISODB are naturally limited by the source of data in the database itself.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Interestingly, this value is very similar to the fraction of outliers identified for adsorption of CO 2 in MOFs as reported by Park et al 458 In addition to that, the authors observed considerable variability in the adsorbed amounts even for materials that are not considered as outliers. 457 Figure 29 depicts the reproducibility map of alcohol isotherm in various porous materials. As shown here, 42 out of 61 systems analyzed by the authors were only moderately consistent (R3).…”
Section: Challenges Of Multiscale Materials Screening: Accuracy Data Availability and Reproducibilitymentioning
confidence: 99%
“…The definitions of reproducibility ( R ) and outlier ( O ) levels, consistency rating, and replicate strength ( S ) can be found in the original article. Reprinted with permission from Bingel et al 457 Copyright 2020 American Chemical Society.…”
Section: Challenges Of Multiscale Materials Screening: Accuracy Data Availability and Reproducibilitymentioning
confidence: 99%
“…The same group extended the analysis in 2020 with focus on alcohols, comparing simulations of methanol and ethanol in four MOFs with the interval of confidence obtained from experimental isotherms via their protocol. 17 In this work, we aim to extend this link to as many gas adsorption isotherms for MOFs as possible, irrespective of the target application: how many MOF identities can we link both to experimentally resolved crystal structures (CSD) and to experimental gas adsorption isotherms (NIST-ISODB) by relying on the metadata present in the two databases?…”
Section: Introductionmentioning
confidence: 99%